Profissão: repórter esportivo - das narrativas da nação ao ofício do jornalista contemporâneo - Rangel, Ana Lúcia de Carvalho (2014)
This dissertation aims to investigate how the contemporary sports reporter relates to football and how this relationship interferes with their craft and construction of journalistic text. More specifically, it seeks to identify practices and the narrative strategies used in the construction of their texts. The study of the elements present in journalistic practice has the perspective that the media actively participated in the construction of the national football imagery and in the contemporary is the great mediator between the public and sporting events. It is in this light that is intended to ascertain how is the relationship with the work of professional press that identifies with its object, examine what is the place of emotion in the composition of sports news and check values that imbue this professional in the construction of journalistic text. The analysis has the corpus of oral history interviews with six journalists who act or have acted as sports reporters at daily newspapers in the city of Rio de Janeiro , all with significant career in sports , which gives them credibility and public authority to star in the constitution memory of Brazilian sports press. The work consists of three steps: 1 ) contextualization - when relating football and Brazilian society, media and sports journalism - ; 2 ) the study of journalism as a profession from the theories of Sociology of Professions and the narrative strategies used in the sportive news in the newspapers ; and 3 ) the qualitative thematic analysis of the interviews .